Собор без крестов-2: [роман] - Шитов Владимир Кузьмич (1997)
Экземпляры: ф.22 (2005) / Инвентарный номер: 49022 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Ш 64 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44